Association of hyperuricemia and pulmonary hypertension: A systematic review and meta-analysis - Uk Kang, Tae; Park, Kyu Yong; Kim, Hyun Jung; Ahn, Hyeong Sik; Yim, Shin-Young; Jun, Jae-Bum (Modern rheumatology, 2019)
Objectives: To investigate the association of hyperuricemia with pulmonary hypertension (PH) in term of subsequent development, severity, and prognosis of PH. Methods: The authors systematically reviewed articles from databases and conducted meta-analyses as follows: (1) association of serum uric acid (UA) levels with the presence of PH; (2) association between serum UA levels and subsequent development of PH, in terms of odds ratio of the development of PH; and (3) association of serum UA levels with severity and prognosis of PH, in terms of pulmonary arterial pressure and hazard ratio of death. Results: Twenty-six studies published between 1999 and 2017 were included. The level of serum UA was higher in subjects with PH than subjects without PH and this finding was observed regardless of status of diuretics use or renal function. The odds ratio of the development of PH was 2.32 (95% CI, 1.05-5.15) in subjects with hyperuricemia. Pulmonary arterial pressure among subjects with PH was also higher in subjects with hyperuricemia than subjects with normouricemia. There was a 19% increased hazard ratio of death (95% CI, 1.06-1.33) among patients with PH who had hyperuricemia. Conclusion: Hyperuricemia is associated with the subsequent development, worse severity and poor prognosis of PH.